Book of Hadith Index and its Significance in Hadith Research - LATHIF RIFA'I (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
This study discusses the development of the hadith index book as a product of hadith codification, from the method and systematic aspect of its preparation. The research is qualitative by using literature study method. The data reasearch has been collected from library documents, primary and secondary data. This study is expected to discover the development of the hadith index book, including the methods and systematics used by the scholars in its compiling. The study finds that the existence of the hadith index book is a response from the scholars to the development of hadith codification. Its existence makes the easiness for hadith reviewers to trace the Prophet's hadith referring to its primary source. In addition, hadith index books have a very close significance to hadith research, especially in the context of takhrîj al-ḥadîs.